STRATEGI PENINGKATAN PERTUMBUHAN EKONOMI MELALUI ANALISIS SEKTOR BASIS DI KOTA BATU PERIODE 2010-2014 - suparta, i made; Nasution, Yohan (JEB17 : Jurnal Ekonomi dan Bisnis, 2018)
ABSTRAKThis research entitled "Strategy of Increasing Economic Growth Through Analysis of Base Sector In Stone Town Period 2010-2014". The purpose of this study is to determine the potential of the region and determine how the steps should be taken in increasing local revenue through the maximization of potential areas owned by the City of Batu. In taking the conclusion of any economic sector that gives real contribution and influence the economic growth that happened in Batu Town, in turn used location quotient analysis method (LQ) and shift-share to obtain concrete data in order to deepen understanding of potential sector owned and knowing shift Economic structure that occurred. This research uses source data in the form of PDRB data. Based on the calculation results through LQ and shift-share analysis, it is known that Batu City has a potential sector. It is also known that Batu City's economy has undergone a shift in structure from the primary sector to the secondary as well as tertiary where in the formation of GRDP continue to increase from year to year and clearly shows a higher growth rate when compared with the primary sector.Â Keywords: Base Analysis, Shift-Share Analysis, Economic Structure Shift Theory